Research progress of pollutants removal from coal-fired flue gas using non-thermal plasma. (January 2017) - Ma, Siming; Zhao, Yongchun; Yang, Jianping; Zhang, Shibo; Zhang, Junying; Zheng, Chuguang
Abstract: Simultaneous removal of multi-pollutants from coal-fired power plants has drawn worldwide attention in recent years. Non-thermal plasma (NTP) flue gas cleaning technologies show good performance on SO2, NOX, and Hg 0 removal and extensive studies have been carried out. This paper reviews the research progress of pollutants removal from coal-fired flue gas using non-thermal plasma. The pollutants removal mechanisms of NTP are briefly described at first. The structure features and parameter characteristics of various NTP reactors are also summarized in this paper. The experimental results of different NTP technologies such as electron beam (EB) irradiation, corona discharge, dielectric barrier discharge (DBD) are reviewed systematically and the effects of flue gas components (O2, H2 O, HCl, NH3, SO2, NO, Hg 0, etc) and oxidation approach on the removal of SO2, NOX, and Hg 0 are discussed comprehensively and systematically. Moreover, the NTP-chemical absorption/catalyst hybrid systems for pollutants removal are involved in this paper as well. The pilot/large-scale demonstration projects of NTP technologies around the world are also summarized in this paper and the development of NTP flue gas cleaning technologies in the future are discussed as well.